2011
DOI: 10.1111/j.1875-595x.2011.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic perceptions amongst educators towards eLearning tools in dental education

Abstract: This paper reports an explorative study about academic educators' perceptions towards learning management systems (LMS) and eLearning tools as used in dental education. Fifty-five educators participated in an online survey which explored their views on eLearning tools within the context of their own professional training background and teaching needs. In general, educators felt that the eLearning LMS (also known as WebCT/Blackboard) was a tool that suited their teaching and learning needs in terms of flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The method tested in this study with the use of the intraoral micro camera, connected directly to video monitors, allows the amplification of the images and facilitates the visualization of the surgical act with all the details of the procedures. This method corroborates the fundamental role of the technology in the current context of the teaching models, increasing and facilitating the levels of learning (8,10,12).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The method tested in this study with the use of the intraoral micro camera, connected directly to video monitors, allows the amplification of the images and facilitates the visualization of the surgical act with all the details of the procedures. This method corroborates the fundamental role of the technology in the current context of the teaching models, increasing and facilitating the levels of learning (8,10,12).…”
Section: Discussionsupporting
confidence: 76%
“…The use of interactive learning methods are now a pedagogical tool to aid learning process (10)(11)(12). This new technology offers new and fascinating tools (computers, video imaging, digitized radiology and electronic data transmission), which are considered to be good resources for the learning process (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The study of academics' beliefs about the integration of technology into higher teaching education has gained impetus in the last ten years. Research on how academics think of using instructional technology shows that they hold elaborate educational opinions that in turn shape teaching and learning [6]. It shows that each educator holds a deep-seated curriculum belief system comprising a wide range of beliefs about students, colleagues, pedagogies and university processes.…”
Section: Academics' Perceptions Of Educational Changementioning
confidence: 99%
“…Some of these characterizations linger more in myth than in reality and have been documented as potential drawbacks. Among them is the possibility that students engage in superficial learning [23] and the perception that lecturer-student personal contact might decrease [6]. Similarly, there is the belief among academics that students will be distracted in class [24] and a concern that students could cheat in examinations using mobile devices [25].…”
Section: Mobile Learningmentioning
confidence: 99%
“…Our study demonstrated little or no improvement in dermatological knowledge, skills, attitudes and satisfaction among healthcare professionals when compared DHE to traditional learning or no interventions. The results are not specific for dermatology area but are also observed in other medical education setting including nursing, neurosurgery training, palliative care, dental education (14,21,(38)(39)(40)(41). Comparable results show the potential of DHE as a complementary or even alternative intervention to traditional learning.…”
Section: Strength and Limitationsmentioning
confidence: 77%